Réponses

2014-05-03T13:26:47+02:00
Bonjour
4x+3y = 206
2x +2y = 114

4x +3 y = 206
-4x - 4y = - 228

-y = -22
y = 22
4x + 66 = 206
4x = 206 - 66
4x = 140
x = 35

Développer et réduire F = (2x - 1)² - (x - 2)(3x - 1)
F = 4x² - 4x + 1 - (3x² -x -6x +2)
F = 4x² -4x +1 -3x² +x +6x -2
F = x² +2x -1

  • Utilisateur Brainly
2014-05-03T13:39:44+02:00
1) systeme
4x+3y=206
2x+2y=114
donc
4x+3y=206
4x+4y=228
par différence
y=22 donc x=35
donc S={(35;22)}

2) équation
F = (2x - 1)² - (x - 2)(3x - 1)
   =4x²-4x+1-(3x²-6x-x+2)
   =x²+3x-1